2004
DOI: 10.1128/iai.72.8.4480-4485.2004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Induces Apoptosis of Human Monocytes but Not Monocyte-Derived Dendritic Cells: Role of the cag Pathogenicity Island

Abstract: Monocytes are circulating precursors of the dendritic cell subset, professional antigen-presenting cells with a unique ability to initiate the innate and adaptive immune response. In this study, we have investigated the effects of wild-type Helicobacter pylori strains and their isogenic mutants with mutations in known bacterial virulence factors on monocytes and monocyte-derived dendritic cells. We show that H. pylori strains induce apoptosis of human monocytes by a mechanism that is dependent on the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
5
19
0
Order By: Relevance
“…Some authors suggest that the apoptotic mechanism possibly involves Fas-bearing T cells through induction of FasL expression (Wang et al, 2000(Wang et al, , 2001. Also, gastric T cells have been reported to express FasL and undergo apoptosis in situ following H. pylori infection as has also been shown previously (Galgani et al, 2004). The role of cag PAI in induction of T cell death through Fas/FasL interaction has also been strongly suggested on the basis that cag PAI-deficient strains of H. pylori were not able to induce apoptosis in T cells (Wang et al, 2001).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some authors suggest that the apoptotic mechanism possibly involves Fas-bearing T cells through induction of FasL expression (Wang et al, 2000(Wang et al, , 2001. Also, gastric T cells have been reported to express FasL and undergo apoptosis in situ following H. pylori infection as has also been shown previously (Galgani et al, 2004). The role of cag PAI in induction of T cell death through Fas/FasL interaction has also been strongly suggested on the basis that cag PAI-deficient strains of H. pylori were not able to induce apoptosis in T cells (Wang et al, 2001).…”
Section: Discussionsupporting
confidence: 54%
“…Low IL-12p40 levels found in the H. pylori cagA+-induced PBMCs of the H. pyloriinfected children and in a lesser degree also in the noninfected children with gastritis may result from two processes. Firstly, a high apoptosis of CD4 + T cells participating in the upregulation of IL-12 production by monocytes, and secondly, hypo-reactivity and/or apoptosis of monocytes directly induced either by H. pylori action (Galgani et al 2004), or indirectly mediated by a relative excess of IL-10 (D'Andrea et al, 1993). Low IL-12 production may play a role in a complex and still poorly understood mechanism of rather limited H. pylori-mediated pro-inflammatory responses usually observed in children (Bontems at al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that infection of H. pylori induces cell apoptosis by Vac A protein (de Freitas et al, 2004;Galgani et al, 2004;Menaker et al, 2004;Cho et al, 2003;Fischer et al, 2004) and Cag A (Isomoto et al, 2010;Maeda and Mentis, 2007). Our previous studies showed the presence of M. hyorhinis and M. fermentans in fresh gastric cancer samples, but whether the infection of these mycoplasmas could directly induce gastric cells apoptosis, ulcer or cancer is unknown.…”
Section: Discussionmentioning
confidence: 84%
“…In a recent study, Galgani et al reported that full induction of IL-1, IL-12, and TNF in human DCs required the expression of cagE (16). CagE is part of the cag PAI and is essential for the proper function of H. pylori type IV secretion system.…”
Section: Discussionmentioning
confidence: 99%